1996
DOI: 10.2466/pr0.1996.78.3.899
|View full text |Cite
|
Sign up to set email alerts
|

Casino Use by College Students

Abstract: College students' gambling behavior (N = 238) at the Foxwoods Resort Casino in Mashantucket, Connecticut was investigated using the South Oaks Gambling Screen. Of the 730 randomly sampled students, 238 returned usable questionnaires, a return rate of 32.5%. Only 35 (14.8%) of the students indicated having visited Foxwoods, of these, 26 (11% of the total) reported having gambled. Rates of problem were relatively low (6 students; 2.5%) and few underage students (3 students; 1.9%) reported using Foxwoods in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Estimates of lifetime prevalence of gambling among college students range from 67% to 97%, with the modal number being 85% (Clarke, 2003;Devlin & Peppard, 1996;Engwall et al, 2004;Ladouceur, Dube, & Bujold, 1994). Huang, Jacobs, Derevensky, Gupta, and Paskus' s (2007a) national study of 20,739 student-athletes reported past year gambling estimates of 62.4% for male athletes and 42.8% for female athletes, which is slightly higher than past year estimates of gambling among students who are not athletes (i.e., 52% for men and 33% for women; LaBrie et al, 2003).…”
Section: Gambling Among College Studentsmentioning
confidence: 99%
“…Estimates of lifetime prevalence of gambling among college students range from 67% to 97%, with the modal number being 85% (Clarke, 2003;Devlin & Peppard, 1996;Engwall et al, 2004;Ladouceur, Dube, & Bujold, 1994). Huang, Jacobs, Derevensky, Gupta, and Paskus' s (2007a) national study of 20,739 student-athletes reported past year gambling estimates of 62.4% for male athletes and 42.8% for female athletes, which is slightly higher than past year estimates of gambling among students who are not athletes (i.e., 52% for men and 33% for women; LaBrie et al, 2003).…”
Section: Gambling Among College Studentsmentioning
confidence: 99%
“…They showed that gambling was more frequent in men and in young subjects (38% of cases). Among students from Connecticut, prevalence of pathological gambling is 2.5% [8]. The accessibility to casinos and slot machines is associated with an increased prevalence of pathological gambling, especially among young subjects [23].…”
Section: Pathological Gamblingmentioning
confidence: 99%
“…Of particular interest are the incidences of underage gambling and the activities that attract these young student gamblers. [1–2] Owing to the inclusive findings of their study, Delvin and Peppard[1] concluded that further study is needed on issues surrounding gamblers, including family background, extent of gambling involvement and reasons for gambling and not gambling among college students.…”
Section: Introductionmentioning
confidence: 99%